An analysis on the association between thermal comfort and visitors' satisfaction in shopping complexes using SEM-PLS / Asniza Hamimi Abdul Tharim ... [et al.] - Abdul Tharim, Asniza Hamimi; Ahmad, Nursaadatun Nisak; Mohamed Saraf, Mohamad Haizam; Che Ahmad, Asmalia; Raffikhul, Nur Qamarina (2021)
This research aims to examine the association between thermal comfort and visitors' satisfaction in shopping complexes. The survey was conducted in selected shopping complexes located at Pulau Pinang, Malaysia. This research was conducted by using a questionnaire survey. It was administered to 176 visitors in the chosen buildings, where respondents were asked to select their preferences based on a five-point Likert scale of agreement and satisfaction. The analysis was conducted using PLS-SEM: SMART PLS Version 3.2 to examine the reliability and validity of the questionnaire. The results indicate that there is a significant relationship between thermal comfort and visitors' satisfaction in shopping complexes, especially with regards to the air movement in the buildings. The results highlight the importance of the thermal comfort condition for visitors' satisfaction in shopping complexes.